Screening for GDM in first trimester of pregnancy and its outcome - Soren, Mamata; Nath, Sudhanshu Sekhar; Tudu, Debananda; Srilekha, Polaki (International Journal of Research in Medical Sciences, 2018)
Background: GDM is associated with increased risk of complications for both mother and fetus both during pregnancy as well as in the postpartum period. Screening for GDM is important to improve short and long term maternal and fetal outcomes. The main purpose of this review is to provide an update on screening for GDM. As per DIPSI criteria women can be diagnosed to have GDM in the first trimester, if the 2hour 75gms OGTT IS 140-199 mg/dL. A prospective observational study with 300 cases was conducted for a period of 1year and 11months (December 2012-2014) in VIMSAR Burla, Sambalpur. Methods: Universal screening was applied by means of DIPSI. Analysis was done by means of t-test, Odd’s ratio, chi squire test. P<.05 was taken as significant. Results: In the present study, 25 cases were diagnosed as GDM with an incidence of 8.33%. Hypertensive disorders of pregnancy (HDP) was found significantly associated with GDM cases (p value 0.02). The mean birth weight in women with GDM (3.05±0.47Kg) was higher than in women with non-GDM (2.65±0.43 Kg). Overall the macrosomia (≥4Kg) rate was 0.67% with 8% in case of GDM mothers. Not a single case of congenital fetal anomaly was detected in the GDM group under our study 20% of the GDM group had their babies admitted to NICU as compared to 17.65% of the non-GDM group (p value 0.76). Conclusions: Women with GDM are at an increased risk for adverse obstetrics and perinatal outcomes. Due to high prevalence of GDM in India early universal screening is essential. Screening for glucose intolerance during the early weeks of pregnancy is beneficial as this policy would help in identifying undiagnosed diabetes prior to conception and to render appropriate care. Screening and diagnosis of GDM with a single test procedure of 75g 2hr PGBS in a non-fasting woman i.e. following DIPSI guidelines is found to be effective, simple, economical and feasible.